Systematic review: Interdisciplinary practices in Agricultural Sciences (Research, Society and Development, 2022)
The interdisciplinarity with its integrative line of action enables the transformation of contents into tangible objects of knowledge. It involves theory-practice-extension and allows reflection and holistic vision. It consists of using knowledge from various disciplines and/or areas to solve a problem or understand a given topic, from different points of view, thus, integrating knowledge and enriching the theme. When it involves practical interculturality, it is at its highest level, called transdisciplinary. Objective: To identify the publications available about interdisciplinary practices in the methodological field of teaching Agricultural Sciences. Methodology: Academic materials published between 2016 and 2021 were selected, based on a systematic review approach from Google Scholar and Dimensions databases. The search terms used were interdisciplinar* OR transdisciplinar* OR contextualiza* AND agro*. Results: 157 materials were selected, of which 43 involved interdisciplinary practices in higher courses in Agricultural Sciences. Among them, only 21 involved practical interculturality. From 2018 to 2021, materials that apply interdisciplinary practices decreased significantly. Conclusion: Interdisciplinary practices are little known and applied in Agricultural Sciences. Theoretically appropriating the theme can contribute to more coherent, engaged, and meaningful pedagogical practices.